2018
DOI: 10.1002/ncp.10065
|View full text |Cite
|
Sign up to set email alerts
|

Successful Placement of Nasointestinal Feeding Tubes Using an Electromagnetic Sensor‐Guided Enteral Access System in Patients With Left Ventricular Assist Devices

Abstract: Technology advances have made it possible to prolong life for patients with heart failure who are not transplant candidates or while awaiting transplant. Many different cardiac devices are available that can be used as a bridge to transplant (temporary support) or as a destination therapy (permanent support). Placement of these devices can cause complications that, if not addressed, could negatively impact the nutrition status of patients. Placement of nasointestinal feeding tubes using an electromagnetic sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…Only patients with EN, associated or not with oral diet therapy can recover the catabolism generated by CHF [ 20 , 21 ]. Other studies corroborate the early onset in stable myocardiopathic patients, around 24 - 48 h after cardiac decompensation [ 2 , 3 , 22 ].…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Only patients with EN, associated or not with oral diet therapy can recover the catabolism generated by CHF [ 20 , 21 ]. Other studies corroborate the early onset in stable myocardiopathic patients, around 24 - 48 h after cardiac decompensation [ 2 , 3 , 22 ].…”
Section: Discussionsupporting
confidence: 56%
“…Enteral diet may be infused continuously or intermittently. Studies have shown that patients who are more debilitated and less active accept diet better via a continuous probe, slowly and for a longer period, even in patients with heart disease [ 2 , 6 , 7 ]. According to the authors, continuous infusion should be decreased if the probability of gastric distension, diarrhea, pulmonary aspiration and metabolic abnormalities exits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations